DETERMINATION OF CARBON IN NATURAL PLUTONIC OLIVINE CRYSTAL - Shilobreyeva S.N.; Kadik A.A.; Minayev V.M.; Kazakov S.S.; Kuz'min L.Y. (My University, 1987)
The authors determined the amount of carbon in plutonic olivines consisting of single crystals from nodules of ultramafic rocks and mineral phenocrysts in rocks of various origin. The determination of carbon in olivine crystals was made by activation analysis, using the reaction 12C(d, n)13N, plus the spectral activation method based on simultaneous activation and recording of the energy spectra of cooccurring particles produced by a competing nuclear reaction, in order to determine surface contamination. Preliminary activation of olivines with deuterons with energies of 1.8 MeV indicated that after a 10-minute interval the positron activity of the specimen resulted only from the decay of 13N. Determination of the structural state of carbon in the olivine specimens by IR spectroscopy indicated that no molecular carbon were present in the crystals. Thus, it appears that F. Freund et al. are correct in asserting that only atomic carbon occurs in the olivine crystal lattice.